1992
DOI: 10.1128/jvi.66.7.4117-4125.1992
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human adenoviruses containing hybrid adenovirus type 5 (Ad5)/Ad12 E1A genes: characterization of hybrid E1A proteins and analysis of transforming activity and host range

Abstract: Hybrid adenovirus type 12 (Ad12)/Ad5 E1A genes were constructed by homologous recombination in Escherichia coli, a technique which offers several advantages over conventional mutagenesis for genetic analysis of proteins. In particular, functional differences between the proteins can be mapped by correlating the replacement of specific sequences with the acquisition of new properties, and there is no requirement for common unique restriction sites or polymerase chain reaction strategies to construct the hybrids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 53 publications
4
22
0
Order By: Relevance
“…As another possible RB-independent mechanism for E1A proteins to transform cells, the binding of Ad5 E1A to the coactivator protein p300 was recently described to correlate with E1A-induced transformation (51). Moreover, it has been shown that the large E1A proteins of Ad12 bind p300 directly and with the same affinity as those of Ad5 (15,27,58). Therefore, we tested the ability of the 13S protein of the transformation-defective Ad12-CS-1 mutant expressed as a GST fusion protein to bind p300 using A549 nuclear extracts; for comparison, we also tested wild-type 13S and ⌬CR2 mutant 13S proteins.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As another possible RB-independent mechanism for E1A proteins to transform cells, the binding of Ad5 E1A to the coactivator protein p300 was recently described to correlate with E1A-induced transformation (51). Moreover, it has been shown that the large E1A proteins of Ad12 bind p300 directly and with the same affinity as those of Ad5 (15,27,58). Therefore, we tested the ability of the 13S protein of the transformation-defective Ad12-CS-1 mutant expressed as a GST fusion protein to bind p300 using A549 nuclear extracts; for comparison, we also tested wild-type 13S and ⌬CR2 mutant 13S proteins.…”
Section: Resultsmentioning
confidence: 99%
“…occurs independent of the RB binding sites, suggesting a different, RB-independent mechanism of transcription regulation and E1A-induced transformation. It has been shown before that despite some variation in the p300 binding sequences of Ad5 E1A and Ad12 E1A, the large E1A proteins of Ad12 bind p300 directly and with the same affinity as those of Ad5 (15,27,58). Since in Ad12 both wild-type E1A and CS-1 mutant E1A are identical in the p300 binding sequence, it is unlikely that the mutant E1A protein does not bind p300.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations